Macronutrient intakes and cardio metabolic risk factors in high BMI African American children - Sharma, Sushma (BioMed Central, 2009)
BACKGROUND: The aim of this study was to evaluate the relationship between intakes of energy-providing macronutrients, and markers of cardio metabolic risk factors in high BMI African American (AA) children. METHODS: A cross sectional analysis of a sample of 9-11 year old children (n = 80) with BMI greater then the 85(th )percentile. Fasting hematological and biochemical measurements, and blood pressure were measured as selected markers of cardio metabolic risk factors and their relationships to dietary intakes determined. RESULTS: After adjusting for gender, pubertal stage and waist circumference (WC), multivariate regression analysis showed that higher total energy intakes (when unadjusted for source of energy) were associated with higher plasma concentrations of intermediate density lipoprotein cholesterol (IDL-C) and very low density lipoprotein cholesterol (VLDL-C). Higher intakes of carbohydrate energy (fat and protein held constant) were associated with higher IDL-C, VLDL-C, triglycerides (TG) and homeostasis model assessment of insulin resistance (HOMA-IR). Higher intakes of fat (carbohydrate and protein held constant), however, were associated with lower IDL-C; and higher protein intakes (fat and carbohydrate held constant) were associated with lower HOMA-IR. CONCLUSION: The specific macronutrients that contribute energy are significantly associated with a wide range of cardio metabolic risk factors in high BMI AA children. Increases in carbohydrate energy were associated with undesirable effects including increases in several classes of plasma lipids and HOMA-IR. Increases in protein energy were associated with the desirable effect of reduced HOMA-IR, and fat energy intakes were associated with the desirable effect of reduced IDL-C. This analysis suggests that the effect of increased energy on risk of developing cardio metabolic risk factors is influenced by the source of that energy.